Nucleus‐Targeted Organoiridium–Albumin Conjugate for Photodynamic Cancer Therapy - Zhang, Pingyu; Huang, Huaiyi; Banerjee, Samya; Clarkson, Guy J.; Ge, Chen; Imberti, Cinzia; Sadler, Peter J. (Angewandte Chemie International Edition, 2019)
An organoiridium–albumin bioconjugate (Ir1‐HSA) was synthesized by reaction of a pendant maleimide ligand with human serum albumin. The phosphorescence of Ir1‐HSA was enhanced significantly compared to parent complex Ir1. The long phosphorescence lifetime and high 1O2 quantum yield of Ir1‐HSA are highly favorable properties for photodynamic therapy. Ir1‐HSA mainly accumulated in the nucleus of living cancer cells and showed remarkable photocytotoxicity against a range of cancer cell lines and tumor spheroids (light IC50; 0.8–5 μm, photo‐cytotoxicity index PI=40–60), while remaining non‐toxic to normal cells and normal cell spheroids, even after photo‐irradiation. This nucleus‐targeting organoiridium‐albumin is a strong candidate photosensitizer for anticancer photodynamic therapy. On target: A nucleus‐targeted organo‐iridium‐HSA conjugate for photodynamic therapy has been developed. Phosphorescence of a weakly emissive maleimide‐functionalized Ir complex is greatly enhanced when conjugated to human serum albumin. The iridium‐HSA conjugate targets the nucleus and generates 1O2 for photodynamic therapy upon irradiation with visible light.